PENGEMBANGAN SISTEM PEMBELAJARAN ONLINE BERBASIS MOODLE DI JURUSAN KURIKULUM DAN TEKNOLOGI PENDIDIKAN UNIVERSITAS NEGERI SEMARANG - Triluqman, Heri; Sukirman, - (Universitas Negeri Semarang, 2009)
The development of e-learning is necessary to support a conventional learningprocess and prepare media to create learning environment that is flexible and easy toaccess. It is expected that e-learning system can increase the frequency of learningprocess, enrich learning materials, and increase student participation in learning. Theobjective of this research is to find out the implementation of MOODLE - basedonline learning system at the Faculty of Curriculum and Educational Technology(Kurikulum dan Teknologi Pendidikan) at Semarang State University. The type ofresearch applied is Research and Development (Penelitian dan pengembangan). Theresults of the research shows that MOODLE - based E-learning wesbsite can beconsidered good. It can be seen from several aspects such as the look and content ofthe website, its implementation, institutional readiness, and facilities andinfrastructure. MOODLE - based E-learning website is recommended to achieve amodel of E-learning in a lecture, initiated by the provision of the media (online ElearningWebsite), and followed by socialization and training of applications.Kata Kunci: pembelajaran online, moodle